Cow's milk allergy in children, from avoidance to tolerance. - Calligaris, Lorenzo; Longo, Giorgio; Badina, Laura; Berti, Irene; Barbi, Egidio (Endocr Metab Immune Disord Drug Targets, 2014)
Food allergy is the primary cause of anaphylaxis in paediatric age affecting roughly 4% of children and their families worldwide, and requiring changes in dietary habits. The prognosis for food allergy in children has traditionally been regarded as good for the most frequent allergens, however the prognosis for cow's milk allergy in the pediatric age is currently considered to be worse than previously believed. There is now enough evidence that measures of avoidance for children at risk did not have any preventive effect whatsoever, but they still came to be counterproductive by avoiding the physiological interaction between food allergens and gastrointestinal mucosal immune system. Programs of specific oral tolerance induction (SOTI) have obtained interesting results in the treatment of food allergy supporting the idea that antigen exposure through gastrointestinal section is important to allow the development of tolerance. Nevertheless this approach is not yet considered "ready" for community recommendations. In this paper we describe our experience in the field of SOTI in children with cow's milk allergy.
Keywords: Animals; Cattle; Child; Child, Preschool; Desensitization, Immunologic; Humans; Immune Tolerance; Milk Hypersensitivity; Milk Substitutes; Retrospective Studies